A grammar of neo-Aramaic : the dialect of the Jews of Arbel - Khan, Geoffrey. (Handbook of Oriental Studies. Section 1 The Near and Middle East, 1999)
Being direct descendants of the Aramaic spoken by the Jews in antiquity, the still spoken Jewish Neo-Aramaic dialects of Kurdistan deserve special and vivid interest. Geoffrey Khan's A Grammar of Neo-Aramaic is a unique record of one of these dialects, now on the verge of extinction. This volume, the result of extensive fieldwork, contains a description of the dialect spoken by the Jews from the region of Arbel (Iraqi Kurdistan), together with a transcription of recorded texts and a glossary. The grammar consists of sections on phonology, morphology and syntax, preceded by an introductory chapter examining the position of this dialect in relation to the other known Neo-Aramaic dialects. The transcribed texts record folktales and accounts of customs, traditions and experiences of the Jews of Kurdistan.